SAT0399 Chronic Antigenic Stimulation and Activity of the Disease Are Predictive of Lymphoma Development in Primary SjÖgren Syndrome: A Case Control Study of 64 Cases. (9th June 2015) - Nocturne, G.; Virone, A.; Le Guern, V.; Hachulla, E.; Daien, C.; Cornec, D.; Vittecoq, O.; Boris, B.; Marcelli, C.; Lavigne, C.; Wendling, D.; Amoura, Z.; et al.
Abstract : Background: Primary Sjögren's syndrome (pSS) is the autoimmune disease with the highest risk of lymphoma. Identification of predictors with this complication is mandatory to allow a more accurate follow-up and to highlight pathogenic pathways involved in lymphomagenesis. Objectives: To define predictors of lymphoma development in pSS patients. Methods: Eighty-two pSS patients who developed lymphoma were included in this retrospective study. Demographic data, clinical and biological features were reviewed. A case-controls study was performed to identify predictors of lymphoma based on the 64 patients who developed lymphoma after pSS diagnosis. These cases were compared to 128 pSS patients without lymphoma randomly selected from the ASSESS cohort. Cases and controls were matched on disease duration and age at lymphoma development or evaluation. The association between lymphoma and disease features was assessed by a Wilcoxon test (continuous data) and a Fisher exact test (categorical data). A multivariate analysis (backward elimination) was performed to identify independent predictors of lymphoma. Results: Among the 82 patients, 71 were women (86.6%) with a mean age ± SD of 57.8±13.1 years. Histologic type was a B cell non Hodgkin lymphoma (B-NHL) in 80/82 (97.6%) with 60 (75%) marginal zone including 47 (58.8) developed from the MALT, 13 (16.2) DLBCL, 2 follicular lymphomas, 2 chronic lymphoid leukemia, 1 chronic EBV-related lymphoproliferation and 2 B-NHL without any details. The most frequent localization was salivary glands (27 cases). A specific treatment was initiated at diagnosis in 68 patients with B-NHL (85%) and remission was obtained in 56 patients. Relapses occurred in 15 patients. Mean disease duration was 8.1±6.6 and 8.7±6.7 years in controls and cases. Predictors of lymphoma are summarized in the table . Clinical parameters associated with lymphoma were history of parotid gland enlargement and purpura. History of arthritis was found to be protective. Biological parameters associated with lymphoma were closely linked to chronic antigenic stimulation: positivity of anti-SSA, rheumatoid factor and cryoglobulinemia, presence of monoclonal component and low C4. Lymphopenia and disease activity (ESSDAI ≥5 and ClinESSDAI≥5 at evaluation before lymphoma (thus not including the weight of lymphoma)) were also associated with lymphoma occurrence. ESSDAI was not included in multivariate analysis because it includes the majority of the features found associated with lymphoma. Multivariate analysis confirmed parotid gland enlargement, RF, cryoglobulinemia and lymphopenia as predictors of lymphoma. History of arthritis was found to be significantly protective. Conclusions: This case-control study of 64 cases of pSS-associated lymphoma highlights the role of chronic antigenic stimulation and disease activity in the development of this severe complication. Disclosure of Interest: None declared